Homeland and nation: Leguia during the centenary of the Battle of Ayacucho - Chaupi Torres, Jose Antonio (2015)
The centenary of 1921 was celebrated under a rhetoric that mainly mixing nationalism with elements of indigenism, hispanism and hispanicamericanism and patriotism with elements of republicanism and Pan-Americanism. On the centenary of 1924 while the nationalist and patriotic speech remains the first will be displaced by the second. This will seek to be studied through the analysis of the speeches delivered by Leguía as well as using the editorials, articles and notes appeared in the two main cultural and entertainment magazines such as varieties and World and complementarily in the daily press. This research will be structured in two parts. In the first part will seek to investigate the cultural political project of the new fatherland, in a second part will study how the official discourse was expressed mostly patriotic base and less nationalist during the celebration of the centenary of the battle of Ayacucho (1924).